2021
DOI: 10.1111/pai.13651
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion and utilization of lipid droplets mediates respiratory syncytial virus‐induced airway hyperresponsiveness

Abstract: Background Respiratory viral infections (RSV) can induce acute asthma attacks, thereby destroying lung function and accelerating the progression of the disease. However, medications in the stable phase of asthma are often not effective for acute attacks induced by viral infections. We aimed to clarify the possible mechanism of viral infection–induced asthma through fatty acid metabolism. Methods and Results The airway resistances, inflammatory injuries, and oxidative stress in the RSV‐induced animal models wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…The relative mRNA expression levels of Gimap5, M6PR, Ecadherin, N-cadherin, Snail, PADI4, Slug, Caspase3 and Caspase9 were subsequently normalized using GAPDH. The data collected were presented as the mean value ± S.D (26).…”
Section: Quantitative Real-time Polymerase Chain Reactionmentioning
confidence: 99%
“…The relative mRNA expression levels of Gimap5, M6PR, Ecadherin, N-cadherin, Snail, PADI4, Slug, Caspase3 and Caspase9 were subsequently normalized using GAPDH. The data collected were presented as the mean value ± S.D (26).…”
Section: Quantitative Real-time Polymerase Chain Reactionmentioning
confidence: 99%
“…Abnormal lipid metabolism plays an important role in the pathogenesis of many diseases. 2 Adiponectin, together with adipocyte size, is the strongest factor associated with insulin resistance in women with PCOS. 3 Metabolic abnormalities are also more prevalent in obese PCOS women.…”
Section: Introductionmentioning
confidence: 99%
“…PCOS is associated with follicle growth arrest, chronic anovulation, minimal granulosa cell proliferation, hyperthecosis with hyperandrogenemia, and insulin resistance. 1 Several studies [2][3][4] have demonstrated that PCOS is a complex and multifactorial disorder involving adipocyte factors. Abnormal lipid metabolism plays an important role in the pathogenesis of many diseases.…”
Section: Introductionmentioning
confidence: 99%
“…For mock infections (the Control group), mice were given an equivalent volume of sterile PBS. 20 The mice were killed on Day 7 of postinfection and their lungs and brain samples were stored at −80°C for follow-up studies. Some samples were sent to Wuhan GeneCreate Biological Engineering Co., Ltd for metabolomics analysis.…”
Section: Mice Experimentsmentioning
confidence: 99%